Search for the Standard Model Higgs boson decaying into b(b)over-bar produced in association with top quarks decaying hadronically in pp collisions at root s=8 TeV with the ATLAS detector - Onofre, A. (2016)
A search for Higgs boson production in association with a pair of top quarks (tt¯H) is performed, where the Higgs boson decays to bb¯¯, and both top quarks decay hadronically. The data used correspond to an integrated luminosity of 20.3 fb−1 of pp collisions at s√=8 TeV collected with the ATLAS detector at the Large Hadron Collider. The search selects events with at least six energetic jets and uses a boosted decision tree algorithm to discriminate between signal and Standard Model background. The dominant multijet background is estimated using a dedicated data-driven technique. For a Higgs boson mass of 125 GeV, an upper limit of 6.4 (5.4) times the Standard Model cross section is observed (expected) at 95% confidence level. The best-fit value for the signal strength is μ = 1.6 ± 2.6 times the Standard Model expectation for mH = 125 GeV. Combining all tt¯H searches carried out by ATLAS at s√=8 and 7 TeV, an observed (expected) upper limit of 3.1 (1.4) times the Standard Model expectation is obtained at 95% confidence level, with a signal strength μ = 1.7 ± 0.8.